OUTREACH SERVICES IN LIBRARIES: A THEORETICAL REVIEW THROUGH LITERATURE STUDY - Putri, Adella; Yolanda, Desri; Anggara, Dwi Yudha; Suhendar, Aris (PERSPEKTIF: Journal of Social and Library Science, 2025)
This study aims to explore strategies for developing library outreach services to enhance social inclusion, reach vulnerable communities, and support sustainable development. The research method used is a qualitative literature review. Data were collected through analysis of literature from reputable journals, academic books, and other credible sources, focusing on mobile library services, digital-based services, community-based programs, and inclusive services for special needs groups. The findings show that outreach services can expand information access, increase community engagement, and empower communities through educational programs. Mobile libraries effectively reach rural communities, while digital services provide convenient access anytime and anywhere. Community-based programs and inclusive services have a significant impact on improving information literacy and supporting community development. However, challenges in implementing these services include budget constraints, infrastructure limitations, and human resource shortages. This research offers practical and theoretical benefits by providing a conceptual framework for managing innovative and sustainable outreach services. The findings are expected to guide libraries in designing service strategies relevant to modern societal needs while promoting social inclusion and sustainability.